2018
DOI: 10.1016/j.foodcont.2018.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumer purchase intentions towards traceable minced beef and beef steak using the theory of planned behavior

Abstract: Recently, traceability labels with a quick response (QR) code have been printed on product packaging to help consumers easily access traceability information through their smart phones. We analyzed consumer (n=616) attitudes and purchase intentions towards traceable minced beef/beef steak in England, and identified psychosocial determinants of their purchase using the theory of planned behavior (TPB). Respondents held a general favorable attitude with positive behavioral beliefs and high trust towards the trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(135 citation statements)
references
References 28 publications
12
120
3
Order By: Relevance
“…The TPB was expanded with new variables such as risk perception (Lobb et al, 2006(Lobb et al, , 2007Spence et al, 2018); health consciousness and environmental concerns (Wee et al, 2014;Yazdanpanah & Forouzani, 2015;Yadav & Pathak, 2016). The extended TPB model was successful in explaining consumers' behavioral intentions in food choices regarding traceable food (Menozzi et al, 2015;Spence et al, 2018) and organic food (Teng & Wang, 2015;Yadav & Pathak, 2016;Demirtas, 2019). However, studies that applied these valuable antecedents of behaviors in the dual context of long-lasting food safety issues and the outbreak of animal diseases (e.g.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The TPB was expanded with new variables such as risk perception (Lobb et al, 2006(Lobb et al, , 2007Spence et al, 2018); health consciousness and environmental concerns (Wee et al, 2014;Yazdanpanah & Forouzani, 2015;Yadav & Pathak, 2016). The extended TPB model was successful in explaining consumers' behavioral intentions in food choices regarding traceable food (Menozzi et al, 2015;Spence et al, 2018) and organic food (Teng & Wang, 2015;Yadav & Pathak, 2016;Demirtas, 2019). However, studies that applied these valuable antecedents of behaviors in the dual context of long-lasting food safety issues and the outbreak of animal diseases (e.g.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…The core variables of the TPB namely attitude, subjective norms, and perceived behavioral control were often found to have positive influences on consumers' intention (Menozzi et al, 2015;Spence et al, 2018;Demirtas, 2019). Among those variables, studies have highlighted attitude as the main determinant of consumers' purchase intentions (Lobb et al, 2007;Choi et al, 2013;Menozzi et al, 2015;Spence et al, 2018).…”
Section: Consumers Value Healthy Eating and Environmental Responsibilmentioning
confidence: 99%
“…Regarding sustainability and the environment, the TPB has been successfully applied in identifying the factors that determine sustainable behaviour in various fields: (a) Reducing contamination and natural resource conservation, such as the intentions to adopt a search engine that promotes sustainable water management [32], using biodiesel by car drivers [33] reducing fine particulate matter emissions [34] and willingness to pay for air quality improvement [35]; (b) recycling and reusing, such as people's intention to separate waste at home [36], reducing waste [37], recycling plastic waste [38], paper waste [39], electrical and electronic waste [40] and industry intentions to recycle food waste [41]; (c) purchasing intention of green products [42], traceable products [43], choosing a sustainable restaurant [15] and staying in green hotels [44].…”
Section: The Theory Of Planned Behaviourmentioning
confidence: 99%
“…It was theorized that consumers with higher levels of interaction will influence the overall acceptability of a product (Ahvenainen & Hurme, 1997;Ampuero & Vila, 2006). It has been reported that a person who was used to looking for information about the country of origin was more likely to accept traceable beef steak marked by quick response (QR) code (Spence, Stancu, Elliott, & Dean, 2018),…”
Section: Current Packaging Interactionsmentioning
confidence: 99%